Metopic synostosis: measuring intracranial volume change following fronto-orbital advancement using three-dimensional photogrammetry - Freudlsperger, Christian; Steinmacher, Sahra; Bächli, Heidi; Somlo, Elek; Hoffmann, Jürgen; Engel, Michael (Journal of cranio-maxillofacial surgery, 2015)
There is still disagreement regarding the intracranial volumes of patients with metopic synostosis compared with healthy patients. This study aimed to compare the intracranial volume of children with metopic synostosis before and after surgery to an age- and sex-matched control cohort using three-dimensional (3D) photogrammetry. Eighteen boys with metopic synostosis were operated on using standardized fronto-orbital advancement. Frontal, posterior and total intracranial volumes were measured exactly 1 day pre-operatively and 10 days post-operatively, using 3D photogrammetry. To establish an age- and sex-matched control group, the 3D photogrammetric data of 634 healthy boys between the ages of 3 and 13 months were analyzed. Mean age at surgery was 9 months (SD 1.7). Prior to surgery, boys with metopic synostosis showed significantly reduced frontal and total intracranial volumes compared with the reference group, but similar posterior volumes. After surgery, frontal and total intracranial volumes did not differ statistically from the control group. As children with metopic synostosis showed significantly smaller frontal and total intracranial volumes compared with an age- and sex-matched control group, corrective surgery should aim to achieve volume expansion. Furthermore, 3D photogrammetry provides a valuable alternative to CT scans in the measurement of intracranial volume in children with metopic synostosis, which significantly reduces the amount of radiation exposure to the growing brain.
Gesehen am 02.05.2017